Screening of medium constituents for clavulanic acid production by Streptomyces clavuligerus - Rodrigues, Kaio César da Silva; de Souza, Arianne Tairyne; Badino, Alberto Colli; Pedrolli, Danielle Biscaro [UNESP]; Cerri, Marcel Otavio [UNESP] (Springer Nature, 2018)
Clavulanic acid is a β-lactam compound with potent inhibitory activity against β-lactamases. Studies have shown that certain amino acids play essential roles in CA biosynthesis. However, quantitative evaluations of the effects of these amino acids are still needed in order to improve CA production. Here, we report a study of the nutritional requirements of Streptomyces clavuligerus for CA production. Firstly, the influence of the primary nitrogen source and the salts composition was investigated. Subsequently, soybean protein isolate was supplemented with arginine (0.0–3.20 g L−1), threonine (0.0–1.44 g L−1), ornithine (0.0–4.08 g L−1), and glutamate (0.0–8.16 g L−1), according to a two-level central composite rotatable design. A medium containing ferrous sulfate yielded CA production of 437 mg L−1, while a formulation without this salt produced only 41 mg L−1 of CA. This substantial difference suggested that Fe2+ is important for CA biosynthesis. The experimental design showed that glutamate and ornithine negatively influenced CA production while arginine and threonine had no influence. The soybean protein isolate provided sufficient C5 precursor for CA biosynthesis, so that supplementation was unnecessary. Screening of medium components, together with experimental design tools, could be a valuable way of enhancing CA titers and reducing the process costs.
Keywords: Amino acids supplementation; Clavulanic acid; Ferrous sulfate; Streptomyces clavuligerus